Library and Information Services (LIS) in astronomical research: an analysis of the contribution of LIS to the historical development of astronomy at the South African Astronomical Observatory - de Young, Theresa (Department of Knowledge and Information Stewardship, 2023)
The objective of the study was to undertake a historical analysis of the contribution of library and information services (LIS) to the South African Astronomical Observatory (SAAO) in the context of the historical development of astronomy in South Africa. Three critical questions guided the study: How has library and information service provision to the SAAO evolved historically in the context of the historical development of astronomy in South Africa?; What is the current status of LIS in astronomical research at the SAAO?; and, What possible new roles could the SAAO Library and its librarians play in an astronomy research facility such as the SAAO to contribute to South African astronomical research? In order to find shared experiences and trends relating to in the field of LIS in astronomical research, data were gathered using semi-structured interviews with purposively selected individuals experienced in the field of astronomical research as well those associated with astronomical LIS; relevant literature sources; primary documents from the SAAO Library archive; and, the researcher's own experiences at the SAAO Library (autoethnography). In adopting a qualitative approach via a phenomenological historical design, the study did not use explicit theory, but anticipated 'theory' in the form of patterns and trends emerging, inductively, at the end of the study out of the data collected. Content analysis together with qualitative research software application, NVivo 12 Pro, were used for analysis and coding of data collected for the study.